Integrasi Sistem Data Kecelakaan Lalu Lintas Di Kabupaten Jember - Kuntoro Bayu Ajie; Harnen Sulistio; Agus Suharyanto (Rekayasa Sipil, 2017)
The rapid development of technology can help people solve their problems faced every day. One of them is the problem in transportation sector related traffic accident data often occur in Jember. Many agencies and institutions that play a role, making the existing data to be different. Traffic accident report from police and patient report in emergency room from hospital is collected from 2012 to 2014. The result of this research is a good integration traffic accident database system between police and hospital using PostgreSQL, an information system about traffic accident recording with the location can be presented in digital map using Microsoft Visual Basic 6.0, and a recommendations to improve the accuracy of existing traffic accident data.